Objective and subjective factors of demographic development of the Republic of Belarus - Zlotnikov, Anatolii G. (Journal of the Belarusian State University. Sociology, 2024)
The demographic processes in the Republic of Belarus that influence the formation of the modern and promising reproductive potential of the state are studied. The objective and subjective factors of depopulation in the country, as well as their interdependence, are analysed. Negative trends in the demographic development of the Republic of Belarus and ways to overcome them are noted. The problems of the implementation of the state demographic policy are described.
Keywords: trends of demographic processes; depopulation; objective and subjective factors of depopulation; reproductive attitudes; migration processes; reproductive potential; demographic prospects of the Republic of Belarus; state demographic policy